Todd Longstaffe-Gowan: The London Town Garden 1740–1840 - Jaine, Tom (Petits Propos Culinaires, 2024)
Todd Longstaffe-Gowan: The London Town Garden 1740–1840: Yale University Press, New Haven and London, 2001: ISBN 0-300-08538-9: 290 pp., b/w photos, h/b, £30.